PENGARUH PENAMBAHAN DAUN KELOR TERHADAP KAJIAN ZAT BESI DAN DAYA TERIMA EKADO TAHU - Tutut Pujianto; Cucuk Suprihartini (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2023)
The majority of teenagers have a poor diet, such as foods high in carbohydrates and fats. They pay less attention to the intake of micronutrients from the food they eat, one of the micronutrients is iron. One of the product development efforts is to modify the snack by adding Moringa leaves as a high-Fe food ingredient in the process of making ekado tofu. This study used an experimental method with a completely randomized design (CRD) using 3 treatments which were then tested for organoleptic acceptance and iron studies. The results showed that based on Friedman's statistical test on the acceptability of the color, aroma, texture, and taste of ekado tofu with the addition of Moringa leaves (P0: 0%, P1: 6%, P2: 8%) showed a significant result < (0.05). The significance of less than indicates that there is a rejection at H0 which means that there is an effect of adding Moringa leaves to the color, aroma, texture, and taste of the resulting ekado tofu product. Iron content in Ekado tofu Moringa leaves treatment 2 with the addition of 8% Moringa leaves got the highest Fe value than the other treatments, namely 1.75 mg, and could meet the daily iron needs of 16% for men and 11.7 for women. % of RDA